Comprehensive transcriptome assessment in PBMCs of post-COVID patients at a median follow-up of 28 months after a mild COVID infection reveals upregulation of JAK/STAT signaling and a prolonged immune response - Fineschi, Serena; Klar, Joakim; Lopez Egido, Juan Ramon; Schuster, Jens; Bergquist, Jonas; Kaden, René; Dahl, Niklas (Frontiers in Immunology, 2025)
BackgroundPost-acute sequelae of SARS-CoV-2 infection (PASC), also known as post-COVID-19 condition (here abbreviated as post-COVID) is an escalating global health issue. The aim of our study was to investigate the mechanisms and clinical manifestations of post-COVID following a mild SARS-CoV-2 infection.MethodsWe analyzed the gene expression profile in PBMCs from 60 middle-aged post-COVID patients and 50 age-matched controls at a median time of 28 months following a mild SARS-CoV-2 infection. The clinical assessments included intensity of post-COVID symptoms, physical and mental fatigue, depression and anxiety. Sixty-seven participants performed a mild exertion ergometer test with assessment of lactate concentrations. Transcriptome analysis was performed on mRNA selected by poly-A enrichment and SARS-CoV-2 RNA fragments were analyzed using the ARTIC protocol.ResultsWe identified 463 differentially expressed transcripts in PBMCs, of which 324 were upregulated and 129 downregulated in post-COVID patients. Upregulated genes in post-COVID individuals were enriched for processes involving JAK-STAT signaling, negative regulation of ubiquitination, IL9 signaling, and negative regulation of viral process, suggesting chronic inflammation. Downregulated genes were enriched for processes involving mitochondrial ATP synthesis, and oxidative phosphorylation, suggesting mitochondrial dysfunction. No SARS-CoV-2 gene fragments were detected in PBMCs of patients with post-COVID and no IFN genes were found differentially expressed in post-COVID patients. Post-COVID was associated with elevated lactate levels in blood, both at rest and after a short recovery phase following exertion, suggesting increased anaerobic activity in skeletal muscles. We did not find differences in the transcriptional profiles or clinical manifestations when comparing patients who contracted the infection from early SARS-CoV-2 variants with those who contracted the infection during the period when the Omicron variant was prevalent.ConclusionsOur findings highlight molecular changes compatible with a persistent immune response in PBMCs of post-COVID subjects at a median follow-up of 28 months after a mild infection, supporting the hypothesis that post-COVID is a chronic inflammatory condition. The upregulation of JAK/STAT signaling suggests a potential therapeutic target in post-COVID.